STUDY OF THE EFFICIENCY OF THE SOFTWARE SECURITY IMPROVING METHOD AND SUBSTANTIATION OF PRACTICAL RECOMMENDATIONS FOR ITS USE - Weiling Cao; Viktor Кosenko; Serhii Semenov (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of research in the article is a way for evaluating the effectiveness of the software security improving method. The aim of the article – study of the effectiveness of the software security improving method and substantiation of practical recommendations for its use. Tasks to be solved: analysis of methods for describing the software security testing process and evaluating its effectiveness, developing a scheme and method for evaluating the effectiveness of a method for improving software security, developing a simulation model for the software security testing process, studying the effectiveness of a method for improving software security, researching and substantiating the reliability of the results obtained, developing practical recommendations for using the method. Applied methods: system analysis, project approach, heuristic methods of decision making, process models. The results obtained: The analysis of the features of the ways for describing the software security testing process and evaluating its effectiveness showed the possibility of taking into account many factors by using the method of dynamics of averages. A way for evaluating the effectiveness of a method for improving software security has been developed, which differs from the known ones by taking into account the scaling factor of the software development process by introducing security testing specialists. With the help of an improved method, the hypothesis of increasing the efficiency of the security process using the developed method by reducing the relative damage indicator at all stages of the software life cycle, depending on the possible duration of a cyber-intrusion, was proved. The substantiation of the reliability of the results of mathematical modeling has been carried out. A number of practical recommendations on the use of the method of improving software security are given and some shortcomings are highlighted, which allow the conclusion that further research is possible.